Dramatic Decline in Cases of Covid-19 in Pakistan: Protective Effects of Wudoo (Ablution: Compulsory Washing of Hands, Arms, Face and Feet) - Awan, Abdul Khalid (International Journal of Pathology, 2020)
From the beginning of August 2020, a remarkable decline in the number of Covid-19 patients in Pakistan was noticed in Pakistan. This phenomenon is in sharp contrast to the epidemiology predictions models by the best institutions of the world for Pakistan. The worst forecast based on a predicted model by Imperial College London produced a scenario of 30,000 deaths a day in early August in Pakistan which would have gone to 80,000 deaths per day in the middle of August. The spread of Covid-19 was expected to follow the same pattern as it was in the West. However, the disease behavior of Covid-19 in Pakistan does not match with countries of similar population and climate. So far, there are 6,000 deaths, with 278,000 recorded cases of infection. While in Brazil (a country with same size of Population as Pakistan) more than 92,000 people have died of Covid-19 and reported case were 2.7 million. In neighboring India on August 5, 2020 reported cases of Corona virus infection were 19,08,254 with 39,820 deaths while infection rate is still on rise.